Translocação de metais pesados em plantas de Melão (Cucumis melo) cultivadas em um Neossolo Quartzarênico do estado do Ceará - Zelaya, Carlos Roberto Irias (2020)
The accumulation of heavy metals in cultivated plants is considered a serious environmental and human health problem, often due to the indiscriminate use of fertilizers and pesticides. Once in plants, metals can accumulate in the organs causing stress and even cell ionic homeostasis disorders, causing plants to develop defense mechanisms to alleviate this stress. To understand these processes, we propose to identify the influence of oxalic and citric acids as well as protein, on the accumulation and translocation of heavy metals present in the rhizosphere, for the different plant organs (root, stem, leaves and fruit) grown from yellow melon, throughout the vegetative cycle in a Quartzarenic Neossol. Soil samples were collected and characterized for their physical-chemical attributes and the levels of copper (Cu), zinc (Zn), lead (Pb) and Cadmium (Cd) were determined. Samples of plant tissue and rhizosphere at 0, 15, 30, 45 and 60 days after transplantation (DAT) were collected, and the levels of heavy metals in the tissues of the plant and rhizosphere were determined as well as the levels of total protein in the tissues and contents of low molecular weight organic acids in the rhizosphere. Subsequently, the transfer factor (TF) and bioaccumulation factor (BF) were calculated. In the rhizosphere, oxalic and citric acids and heavy metal contents higher than those in the soil were detected. In the plant, high levels of Pb and Zn were detected at 45 DAT, at the root, Cu remained stable throughout the studied period and Pb showed its highest levels at 15 DAT, on the leaf, Cu had its peak at 45 DAT. The fruit and stem in general, presented low levels of metals and Cd presented its highest levels at 0DAT in the root, stem and leaf. The BF and TF showed values higher than one (BF and TF> 1), this value being indicative of the plant's potential for phytoextraction in several stages of planting, mainly for metals Cu and Zn. In general, organic acids and protein showed correlations with the levels of heavy metals in the different organs of the plant. From the data obtained, it was concluded that the protein content in the plant tissues and the levels of oxalic and citric acid released by the plant in the rhizosphere increase or decrease the absorption, accumulation and translocation of Cu, Zn and Pb in the different organs of the plant. yellow melon